(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses about the relationship between folklore and written literature, in particular, it reveals the simple and complex folklorisms, folk motives in the epic “Korasoch”, proves the importance of common Turkic samples of oral folk art. Beside the author discloses the ways and methods of creative use of folkloristic traditions in the works of Tura Suleiman and the influence of folklore to the works of specific authors.